Pseudohypertriglyceridemia in a Patient with Pancreatitis Without Evidence for Glycerol Kinase Deficiency: A Rare Case Report and Review of the Literature - Jianping Zhu; Chunjuan Zhang; Rui Zhao (Diseases)
Background: Pseudohypertriglyceridemia (pseudo-HTG) is a condition in patients with glycerol kinase deficiency or other disorders of glycerol metabolism, as well as in individuals with alcoholism, severe liver disease, or metabolic disturbances, and those receiving heparin therapy. Exogenous glycerol intake can also trigger this condition. However, the causes of pseudo-HTG are poorly understood, and a clinical algorithm for its diagnosing remains to be developed. Case presentation: We present the case of a 46-year-old man admitted to hospital with hypertriglyceridemia-induced severe acute pancreatitis (HTG-SAP) and type 2 diabetes mellitus. Upon admission, his plasma triglyceride (TG) level was critically high at 43.78 mmol/L (3877 mg/dL). During hospitalization, he developed acute renal insufficiency and diabetic ketoacidosis (DKA). Despite conventional lipid-lowering treatments, including extracorporeal lipoprotein apheresis, his TG levels remained elevated. The unusually clear serum led to suspicion of pseudo-HTG. A glycerol-corrected TG assay confirmed normal TG values, thereby diagnosing pseudo-HTG. Conclusions: This report presents the first confirmed case of pseudo-HTG verified through definitive glycerol kinase (GK) gene testing in a patient without glycerol kinase deficiency. We also include a review of the relevant literature and propose a clinical algorithm. The case report highlights the importance of considering pseudo-HTG in hypertriglyceridemia patients who do not respond well to the standard TG-lowering treatment. Our proposed clinical algorithm for diagnosing pseudo-HTG is potentially invaluable in clinical practice, and helps to prevent unnecessary lipid-lowering treatments for patients with pseudo-HTG.